2018
DOI: 10.9734/ijpss/2018/43348
|View full text |Cite
|
Sign up to set email alerts
|

Production of Seedlings of Fast - Growth Tree of Paulownia elongata S. Y. Hu

Abstract: The major method of propagation of varieties and hybrids of Paulownia elongata is vegetative (asexual) method. Paulownia elongata can be propagated by macropropagation techniques (root cuttings, green cuttings and by micropropagation technique, tissue culture or in vitro. Today the tissue culture method is the most modern biotechnological method. In Bosnia and Herzegovina and regions of former Yugoslawia, more and more Paulownia elongata seedlings are being produced and new plantations of Paulownia elongata ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Propagation of paulownia is possible by seed, stem and root explants. The slow rate of growth and poor germination of seeds encourage the in vitro propagation of paulownia (Ipekci andGozukirmizi, 2003 andHamza, 2019).Consequently, the results showed that the tissue culture technique offers a rapid mean of propagation of paulownia by maintaining the genetic gain (Bergmann andMoon, 1997 andSalki et al, 2018). Accordingly, in this investigation, nodal explants considered an excellent explant source for direct micropropagation protocol of Paulownia tomentosa in Egypt.…”
Section: Resultsand Disscution 1 In Vitro Culturementioning
confidence: 75%
“…Propagation of paulownia is possible by seed, stem and root explants. The slow rate of growth and poor germination of seeds encourage the in vitro propagation of paulownia (Ipekci andGozukirmizi, 2003 andHamza, 2019).Consequently, the results showed that the tissue culture technique offers a rapid mean of propagation of paulownia by maintaining the genetic gain (Bergmann andMoon, 1997 andSalki et al, 2018). Accordingly, in this investigation, nodal explants considered an excellent explant source for direct micropropagation protocol of Paulownia tomentosa in Egypt.…”
Section: Resultsand Disscution 1 In Vitro Culturementioning
confidence: 75%